Defining Reading Skills and Strategies in Formulating a Model for Teaching Reading in Indonesion Context - Melyann Melani (Universitas Negeri Padang, 2014)
In order to formulate a suitable and effective model for teaching reading in Indonesian context there are two important things that need to be considered, they are; a clear definition of what reading is which leads to the differences between reading skills and strategies and also a discussion on the differences between reading in first language, second language and foreign language. A comprehensive definition of reading will be able to answer questions on what fluent readers do when they read, what process are used by fluent readers and how do these process work together to build meaning. The answer to the questions above will also lead to the identification of reading skills. Reading strategies on the other hand, is another different concept that should be clarified when someone intended to make scientific consideration in making decision on what reading skills and strategies are needed by their students. After deciding what reading skills and strategies are important, the way how to teach them is also an important issue that should be addressed. The position of English as a foreign language in Indonesia is seen as obstacle for students and it needs special attention. As compared to reading in foreign language, there has been a wide range of literature on the comparison between reading in first and second language. It would be beneficial to discuss reading in foreign language since it will shed ideas on how to teach reading in Indonesian context. Therefore, this article will try to discuss a comprehensive definition of reading, reading skills and strategies and also discuss important point on reading in first, second and foreign language. Finally, the writer will purpose a model for teaching reading which is expected to be suitable for Indonesian students.